Caribbean Women Poets - Disarming Tradition - Christine Harris (Miscelánea: A Journal of English and American Studies)
This article sets out to explore the way in which women writers of Caribbean origin express various concerns relating to their heritage through poetry which encompasses not only their position as women seen from a feminist perspective but also from historical and contemporary positions in contrasting societies. It argues that an overall need to find an identity linked to the past is paramount for establishing a position for women in the future, and that the poetry achieves this through breaking with the traditional notions of women and poets. The article focuses particularly on the work by Grace Nichols and Loma Goodison.